Structural Transformations of Emerging Organic Contaminants (EOCs) by Halophilic and Acidophilic Microorganisms - Razia, Sultana (Curtin University, 2024)
The halophile was identified as Marinobacter sp that could degrade about 70% ibuprofen (IBU) at a concentration of 50 mg L-1 and above 30% bisphenol A (BPA) at a concentration of 20 mg L-1 within five weeks at 8% NaCl. The acidophile was identified as Tichosporiella sp, which could degrade about 80% IBU and about 90% BPA at a concentration of 50 mg L-1 within five weeks at pH 5.5.